SEO warrior - Jerkovic, John I. (O'Reilly Media, 2010)
How can you make it easier for people to find your website? And how can you convert casual visitors into active users? SEO Warrior shows you how it's done through a collection of tried and true techniques, hacks, and best practices. Learn the nuts and bolts of search engine optimization (SEO) theory, the importance of keyword strategy, and how to avoid and remedy search engine traps. You'll also learn about search engine marketing (SEM) practices, such as Google AdWords, and how you can use social networking to increase your visibility. Ideal for web developers, savvy marketers, webmasters, an.